2011
DOI: 10.1016/j.bbmt.2010.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis with Sirolimus and Tacrolimus ± Antithymocyte Globulin Reduces the Risk of Acute Graft-versus-Host Disease without an Overall Survival Benefit Following Allogeneic Stem Cell Transplantation

Abstract: Methotrexate (MTX) is a standard agent used in combination with calcineurin inhibitors for graft-versus-host disease (GVHD) prophylaxis in patients undergoing allogeneic hematopoietic cell (HCT) transplantation. We retrospectively compared the incidence of acute GVHD (aGVHD), transplant-related morbidity, and mortality in patients given sirolimus/tacrolimus ± antithymocyte globulin (ATG) versus MTX/tacrolimus or cyclosporine and allogeneic transplantation for hematologic malignancies. Between January 1, 2005, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…These results are in agreement with a retrospective study in which the incidence of TA-TMA in patients who were given TAC/SIR ± ATG was not significantly different from that in patients who received MTX with TAC or CYA (10.2% vs 4.3%), 23 or with those of a recently randomized phase II trial comparing TAC/SIR with TAC/MTX, 24 although the high incidence of TA-TMA reported in this latter trial (24.3% with TAC/SIR and 18.9% with TAC/MTX) should be noted. 24 Endothelial cells can be activated and damaged by several factors after HSCT.…”
Section: Baseline Characteristics Of Patientssupporting
confidence: 82%
See 2 more Smart Citations
“…These results are in agreement with a retrospective study in which the incidence of TA-TMA in patients who were given TAC/SIR ± ATG was not significantly different from that in patients who received MTX with TAC or CYA (10.2% vs 4.3%), 23 or with those of a recently randomized phase II trial comparing TAC/SIR with TAC/MTX, 24 although the high incidence of TA-TMA reported in this latter trial (24.3% with TAC/SIR and 18.9% with TAC/MTX) should be noted. 24 Endothelial cells can be activated and damaged by several factors after HSCT.…”
Section: Baseline Characteristics Of Patientssupporting
confidence: 82%
“…[17][18][19]21,22 In a recent phase II multicenter prospective trial conducted by our group, including some of the patients in this study, no differences were observed in the incidence of TA-TMA when TAC/SIR was compared with patients included in a prior prospective trial using CYA-mycophenolate (the overall incidences of TA-TMA were 10% and 6%, respectively). 25 In addition, very few studies 23,24 have evaluated the risk of TA-TMA among patients receiving the TAC/SIR combination in comparison with other TAC-based regimens. To shed further light on this matter, we performed a retrospective analysis in 102 allogeneic HSCT recipients who consecutively received TAC/SIR (n ¼ 68) or TAC/MTX ± ATG (n ¼ 34) for GVHD prophylaxis.…”
Section: Baseline Characteristics Of Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The administration of rapamycin has recently been shown to possibly decrease the severity of GVHD. 31 This observation tallies with our gene expression analysis.…”
Section: Discussionmentioning
confidence: 87%
“…The mTOR [mechanistic target of rapamycin (serine/threonine kinase)] inhibitor sirolimus has been used extensively for the prevention and treatment of graft-versus-host disease (GVHD) after allogeneic haematopoietic stem cell transplantation (HSCT)(Alyea, et al 2008, Antin, et al 2003, Benito, et al 2001, Couriel, et al 2005, Cutler, et al 2004, Cutler, et al 2007, Furlong, et al 2008, Ho, et al 2009, Johnston, et al 2005, Jurado, et al 2007, Perez-Simon, et al 2013, Rodriguez, et al 2010, Rosenbeck, et al 2011). A randomized phase II trial in patients receiving mostly myeloablative HSCT suggested a benefit to tacrolimus/sirolimus (Tac/Sir) over tacrolimus/methotrexate (Tax/Mtx)(Pidala, et al 2012) in terms of acute GVHD prevention; however, a phase III randomized trial (Blood and Marrow Transplantation Clinical Trial Network [BMT CTN] 0402) comparing those 2 regimens in patients undergoing myeloablative HSCT from matched related donors for acute myeloid leukaemia, myelodysplastic syndromes or acute lymphoblastic leukaemia (ALL) showed no significant difference in acute GVHD (aGVHD)-free survival (Cutler, et al 2012), despite a trend towards lower rates of aGVHD.…”
Section: Introductionmentioning
confidence: 99%